2018
DOI: 10.3390/recycling3030032
|View full text |Cite
|
Sign up to set email alerts
|

Study of Temperature Fields and Heavy Metal Content in the Ash and Flue Gas Produced by the Combustion of Briquettes Coming from Paper and Cardboard Waste

Abstract: The present study focused on the combustion of four types of briquettes made from paper and cardboard waste produced in Ouagadougou (Burkina Faso). Rotary and tubular kilns were used to study the combustion. The combustion mean temperatures, nitrogen, phosphorus and potassium (NPK) content in the ash and heavy metals content in the ash and the flue gas were analyzed. The combustion steady phase mean temperatures ranged from 950 °C to 750 °C were obtained according to briquettes type. The temperature favored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The amount of nitrogen in the hydrolysate is insufficient to support biomass growth. A recent study [ 49 ] reported a low 0.003% nitrogen content in corrugated carboard acidic hydrolysate. Since high nitrogen concentrations directly increase cell biomass rather than PHA formation [ 50 ], PHA generation and cell proliferation were severely hindered.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of nitrogen in the hydrolysate is insufficient to support biomass growth. A recent study [ 49 ] reported a low 0.003% nitrogen content in corrugated carboard acidic hydrolysate. Since high nitrogen concentrations directly increase cell biomass rather than PHA formation [ 50 ], PHA generation and cell proliferation were severely hindered.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of pens made of cardboard, there is no study made directly with this material to find its macronutrient content, however if there is an investigation where its NPK content is analyzed by burning it cardboard briquettes to get its ashes, however the result is that its content is lower than required by the standard UNE-EN ISO 16967:2015 [31], to be considered fertilizer [32].…”
Section: A Diagram Of the Use Of Pen As Fertilizer Materialsmentioning
confidence: 99%
“…The amounts of trace elements released when burning waste paper and corrugated cardboard increases with temperature [78]. When burning paper at 750-950 °C, manganese (68-205 mg/kg of fuel) and lead (38-54 mg/kg o pass into flue gas [78]. In our case, the amount of Mn released into the air was abou as high, with input paper briquettes containing Mn in concentrations up to 520 The combustion in the EC2 and EC3 boiler released Mn in amounts of 300 to 470 of fuel and Pb in amounts of 18 to 20 mg/kg of fuel.…”
Section: Pb Wm CD Bec2 > Bec3 Bec3 > Bec2 Bec2 > Bec3 Bec3 > Bec2 Bec2 > Bec3 Bec3 > Bec2mentioning
confidence: 99%
“…In the case of printed cartons, the content of other elements of Sn and Sb is also increased in the flue gas [77]. The amounts of trace elements released when burning waste office paper and corrugated cardboard increases with temperature [78]. When burning waste paper at 750-950 • C, manganese (68-205 mg/kg of fuel) and lead (38-54 mg/kg of fuel) pass into flue gas [78].…”
Section: Pb Wm CD Bec2 > Bec3 Bec3 > Bec2 Bec2 > Bec3 Bec3 > Bec2 Bec2 > Bec3 Bec3 > Bec2mentioning
confidence: 99%
See 1 more Smart Citation